2021
DOI: 10.1021/acs.biochem.1c00161
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam as a Probe for Drug–Drug Interactions Mediated by CYP3A4: Homotropic Allosteric Mechanism of Site-Specific Hydroxylation

Abstract: We developed an efficient and sensitive probe for drug–drug interactions mediated by human CYP3A4 by using midazolam (MDZ) as a probe substrate. Using global analysis of four parameters over several experimental data sets, we demonstrate that the first MDZ molecule (MDZ1) binds with high affinity at the productive site near the heme iron and gives only hydroxylation at the 1 position (1OH). The second midazolam molecule (MDZ2) binds at an allosteric site at the membrane surface and perturbs the position and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 52 publications
5
56
0
Order By: Relevance
“…Very recently, Sligar et al . reported the allosteric pathway in midazolam (MDZ) hydroxylation by CYP3A4, showing that the allostery could also alter the product pattern (1OH vs. 4OH of MDZ) [40] . Hackett, Atkins and the co‐workers described the allosteric interactions at the molecular level with the self‐assembled CYP3A4 nanodiscs.…”
Section: Substrate‐regulated P450s Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Sligar et al . reported the allosteric pathway in midazolam (MDZ) hydroxylation by CYP3A4, showing that the allostery could also alter the product pattern (1OH vs. 4OH of MDZ) [40] . Hackett, Atkins and the co‐workers described the allosteric interactions at the molecular level with the self‐assembled CYP3A4 nanodiscs.…”
Section: Substrate‐regulated P450s Catalysismentioning
confidence: 99%
“…[38,39] Very recently, Sligar et al reported the allosteric pathway in midazolam (MDZ) hydroxylation by CYP3A4, showing that the allostery could also alter the product pattern (1OH vs. 4OH of MDZ). [40] Hackett, Atkins and the co-workers described the allosteric interactions at the molecular level with the self-assembled CYP3A4 nanodiscs. They found that the allosteric ligand remained dynamic at the Phe-cluster binding site in the FÀ G region, which located at the interface of enzyme and membrane.…”
Section: Allosteric Regulationmentioning
confidence: 99%
“…Two of these molecules are accommodated inside the substrate-binding pocket, while the third interacts with CYP3A4 at the protein–membrane interface at the pocket formed between the F-F’ and G-G’ loops on one side and lipid head groups on another. This was confirmed by the effect of mutations at the residues 212–215 [ 25 , 26 ], and by the binding of covalently linked dimers of TST at the substrate-binding pocket and the allosteric effect caused by TST monomer [ 28 ]. The binding of TST and PGS at this peripheral site with high affinity is also corroborated by two X-ray structures [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 97%
“…Importantly, experimental protocols for in vitro studies should provide quantitative and reproducible measurements of essential biochemical parameters, such as catalytic rates and binding constants. The incorporation of heterologously expressed CYP3A4 in lipid nanodiscs allows one to obtain an array of data supporting the general mechanistic understanding of homotropic and heterotropic cooperativity in CYP3A4 [ 10 , 11 , 24 , 25 , 26 , 27 ] by defining the inherent properties of states with differing number of molecules bound. Based on previous results obtained with substrates and effectors such as (i) testosterone (TST) and alpha-naphthoflavone (ANF) [ 27 ]; (ii) progesterone (PGS) and carbamazepine [ 11 , 25 ]; and (iii) atorvastatin and dronedarone [ 10 ], the general picture of homotropic and heterotropic interactions of substrates and effectors in CYP3A4 is available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation